2013
DOI: 10.1007/s13149-013-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Abandons de prophylaxie post-exposition au Centre antirabique d’Abidjan, Côte d’Ivoire

Abstract: Despite the availability of effective anti-rabies vaccine, rabies keeps affecting people in developing countries such as Côte d'Ivoire. The low compliance with Post Exposure Prophylaxis (PEP) partially explains this situation. This study was aiming at studying the reasons to abandon PEP. This descriptive and cross-sectional study has taken place at the anti-rabies Center of Abidjan from October 1st to December 2009. Data were collected in two steps: we first interviewed all the patients at the anti-rabies cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
9
0
4
Order By: Relevance
“…We found a surprisingly high adherence to completion of vaccine administration; 54% of animal-bite patients completed all five doses in our study. In contrast, lower adherence was reported in Iran (16.3%-18.7%), Tanzania (28%), and Cote d’Ivoire (47.3%) [ 6 , 8 , 19 , 20 ]. Two studies in Nigeria had similar or higher completion coverage rates among animal-bite patients identified through a rabies lab registry and a pediatric hospital (60.7%) [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 95%
“…We found a surprisingly high adherence to completion of vaccine administration; 54% of animal-bite patients completed all five doses in our study. In contrast, lower adherence was reported in Iran (16.3%-18.7%), Tanzania (28%), and Cote d’Ivoire (47.3%) [ 6 , 8 , 19 , 20 ]. Two studies in Nigeria had similar or higher completion coverage rates among animal-bite patients identified through a rabies lab registry and a pediatric hospital (60.7%) [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 95%
“…As demonstrated in this study, poor patient compliance (56.6%) with the multi-dose regimens currently in use continues to be a problem that increases the risk of developing rabies after exposure. In Côte d’Ivoire, the most frequent reasons for not completing the immunization schedule have been financial, in that animal owners refused to pay for treatment or that patients were unable to pay for it, though other factors such as awareness and clinic proximity were also responsible [ 21 ]. Other impediments to compliance have been reported to include loss of wages, forgotten dates and the distance and time needed to travel to the clinic [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found no other studies that had stratified adherence into these categories, which makes direct comparison of findings challenging. In studies that have reported adherence in countries with endemic rabies, it has been poor, with rates as low as 28% in Tanzania, 40% in Nepal, and 48% in the Ivory Coast, 1923 and only reaching 60% in Bhutan. 22 Among respondents in our survey who sought medical care and for whom a rabies exposure could not be ruled out, 58% completed at least four doses of vaccine, with the proportion being 81% among those with confirmed or probable exposures.…”
Section: Discussionmentioning
confidence: 99%